Obstructive Sleep Apnea (OSA) dan Hubungannya dengan Defisiensi Vitamin D - Dandy Fahsi Algifary (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
It is estimated that as much as 2-4% of the total middle-aged population suffer from sleep apnea, with a trend towards men compared to women. The long-term effects of Obstructive Sleep Apnea (OSA) include impaired cognitive function, insulin resistance, cardiovascular disease, and depression. Research on the relationship between vitamin D and OSA severity has become an important concern because vitamin D deficiency is also a common medical problem worldwide, and its prevalence is increasing with obesity, sedentary lifestyles, limited sun exposure, and aging. The purpose of this literature study was to determine the relationship between OSA and the presence of Vitamin D deficiency. The literature sources used in this literature study involved 17 libraries from 1 national journal and 16 international journals. Various studies have shown an association between vitamin D deficiency and OSA caused by complex pathogenetic mechanisms and influenced by several confounding factors. Patients with severe OSA are generally associated with vitamin D deficiency.